HUBUNGAN ANTARA DISIPLIN, MANDIRI, INTERAKSI EDUKATIF DAN MINAT BELAJAR DENGAN HASIL BELAJAR MATEMATIKA DI SEKOLAH DASAR - Susintoi, Susintoi; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the correlation between discipline, independence, educational interaction, and interest in learning with learning outcomes; the relationship together with learning outcomes; and the percentage of combined contributions to mathematics learning outcomes. This research uses a descriptive method with a quantitative approach implemented in class III SD Negeri 07 Pontianak Utara. The number of samples were 84 children. Data collection was carried out using a questionnaire. Determination of the correlation between the four variables namely discipline, independence, educational interaction, and interest in learning with mathematics learning outcomes using simple correlation (r) and the correlation together using the multiple correlation (R) Doo Little technique. The results showed a positive and significant correlation between predictor variables and criterion variables obtained r1y of 0.409, r2y of 0.436, r3y of 0.366, r4y of 0.499, and a joint relationship between predictor variables and learning outcomes obtained R of 0.597 with the largest contribution namely the variable interest in learning by 18%, followed by discipline 11%, independent 5%, educational interaction 1%, and a combined contribution of 36%.Keywords: Discipline, Independence, Educative Interaction, Interest In Learning, Mathematics Learning Outcomes